Gender, Generations and the Family in International Migration - Kraler, Albert (Amsterdam University Press, 2011)
Family-related migration is moving to the centre of political debates on migration, integration and multiculturalism in Europe. It is also more and more leading to lively academic interest in the family dimensions of international migration. At the same time, strands of research on family migrations and migrant families remain separate from - and sometimes ignorant of - each other. This volume seeks to bridge the disciplinary divides. Fifteen chapters come up with a number of common themes. Collectively, the authors address the need to better understand the diversity of family-related migration and its resulting family forms and practices, to question, if not counter, simplistic assumptions about migrant families in public discourses, to study family migration from a mix of disciplinary perspectives at various levels and via different methodological approaches and to acknowledge the state's role in shaping family-related migration, practices and lives.